The Reactionary Nature of Poe's Gothic Tales - Johnston, Jane (My University, 1995)
Poe has been celebrated as a genius and deprecated as a plagiarist. Some see him as a symbolist while others regard him as a candidate for psychoanalysis. Despite the variety of critical approaches, however, the label of "Gothic" is often applied to Poe's tales. His stories do contain typical Gothic paraphernalia and settings, but this paper examines instead the extent to which Poe's stories express an ambivalent attitude, common to Gothic literature, in reaction to social changes occurring in America.
Gothic fiction was seen by many as a revolutionary form due to its tendency to collapse long-established boundaries and to promote new subject matter. Yet Gothic can also be called a reactionary form. Coming at a time when absolute monarchy in Europe was starting to be replaced by more democratic systems, this type of literature often responded with stories of individuals who, although perhaps heroic in their uniqueness and desire for knowledge and power, were almost inevitably damned.
America in the early to mid 1800's was dealing with many of the same issues. Individualism of both the country and the common man was hailed, much to the dismay of many who felt that this led to isolation and a loss of community. In many of Poe's tales the focus is on an alienated, solitary hero who perhaps willingly but inevitably steps outside the boundaries of society. This leads not to independence, but isolation and torment. By losing touch with everyday reality one may gain revelations or transcendental experiences, but these experiences end in madness and death for Poe's characters.
In many ways Poe's tales seem to suggest the dangers of progressive individualism. This paper involves a close reading of Poe's tales in order to determine the extent to which they may be considered examples of reactionary Gothic literature.
Keywords: English Language and Literature; English Language and Literature